The Influence of Understanding Project Management and Construction Implementation on the Success of Electricity Projects : JEL classification: H54, L94, O22, M12, C30 - Dwi Nugroho; Mujahid Yunus; Abdul Majid Bakri (Journal La Bisecoman, 2025)
In contemporary times, management has become a crucial asset for the functioning of an organization, thus warranting greater attention. Over the past two years, PT PLN UIP Sulawesi has experienced an expansion of its responsibilities; initially focused solely on infrastructure development in accordance with the RUPTL and catering to community customers, it has now taken on additional duties. These include the construction of electrical infrastructure for high-voltage customers, particularly for smelter clients located in Sulawesi. In light of this phenomenon, the researcher aims to conduct a study to ensure that future projects are completed in accordance with the stipulated time, quality, and budget. The objective. of this research is to analyze the understanding of project management and construction implementation in relation to the success of electricity projects at PLN UIP Sulawesi. This study.is quantitative in nature, involving the distribution of questionnaires.to 107 respondents from a population of 146 project teams at PT PLN UIP Sulawesi. Data analysis in this research is conducted using path analysis. The results indicate that both the understanding of project management and construction implementation have a positive and significant simultaneous effect on project success.